"My mother in-law forced my husband to divorce me": Experiences of women with infertility in Zamfara State of Nigeria. - Florence Naab; Yakubu Lawali; Ernestina S Donkor (PLoS ONE, 2019)
Introduction Women with infertility have different experiences that determine the quality of their psychosocial health. Cultural constructions of infertility in Africa have made the experience of infertility among African women more burdensome. Yet, little is known about the psychosocial experiences of women with infertility in Zamfara State of Nigeria. The purpose of this study was to explore the psychosocial experiences of women with infertility in Zamfara. Materials and methods An exploratory qualitative design was used for this exploration. Individual in-depth interviews were conducted using a semi-structured interview guide. Ethical approval was received from the Institutional Review Board of the Nogouchi Memorial Institute for Medical Research in the University of Ghana. Women who were married and seeking treatment for infertility from a public hospital were recruited and interviewed. A total of 12 women were interviewed with each interview lasting 45 minutes. The interviews were audiotaped with permission from the participants, transcribed verbatim, and content analysed. Results The findings revealed that psychologically, majority of the women had experienced anxiety, stress and depression as a result of their inability to get pregnant. Socially, the women suffered self and social isolation, social stigma, social pressure and marital problems. Conclusion These women have psychosocial health problems that need the attention of health professionals to enhance their wellbeing.